Person-Situation Predictors of Maximum and Typical Performance. - Witt, L.A.; Spitzmüller, Christiane (Human Performance, 2007)
We examined the main and interactive effects of general mental ability (GMA) and perceived organizational support (POS) on typical performance and maximum performance. Data from two field samples (96 programmers and 181 cash vault employees) empirically supported distinguishing between typical performance and maximum performance. GMA was related to maximum performance but not to typical performance, and POS was related to two out of three measures of typical performance. Interactive effects of GMA and POS were detected in both samples for maximum performance outcomes but not found for typical performance outcomes.